Effects of Organizing Creative Art Activities on Kindergartners’ Abilities to Use Fine Motor Skills and Language - Singkru, Praphasiri; Thamsirikwan, Phochet; Koolnapadol, Aungkana (Journal of Graduate Research, 2020)
The objective of this semi-experimental research was to compare the kindergarteners’ language and fine motor abilities after having undergone through the creative art activities between the experimental group and the control one. The sample group consisted of 60 male and female kindergarteners, aged between 3 and 4 years and studying in Kindergarten 1/1 and 1/2 in the second semester of the 2019 academic year at Watsothornwararam School, Muang district, Chachoengsao province. The cluster sampling method was applied to select the sample group and they were assigned as an experimental group and a control group with an equal number by applying the matching technique. The research instruments consisted of were composed of the creative art activity experience management plans and the assessment in using fine motor ability and language of the kindergarteners. The data were statistically analyzed for mean and standard deviation, and the independent t-test was applied to test the research hypotheses. The research results revealed the fine motor abilities and language of the experimental group having undergone the creative art activities were significantly higher than those of the control group at the .05 level.